Marketing in Global Economic Turbulence - Role of B-Schools in Grooming Management Graduates - Rama Prasad, M. V. (Indian Journal of Marketing, 2011)
As the international economic crisis continues to unfold, its effects are being felt across all sectors of the economy. With the failures of major financial firms, the ongoing decline of the auto industry, the efforts at a government response, and speculation about a new regulatory structure, major changes are afoot in the marketplace. Business faculty is becoming increasingly aware that these market changes may have serious effects for the business curriculum as well. Indeed, with the recent increase in MBA program applications, an altered curriculum may reach a greater than ever number of future managers. The economic crisis challenges faculty to use their research to make sense of its causes and effects, and to use their teaching to help students understand current events while preparing them as managers in a changed landscape. This paper examines how business faculty are responding to the economic crisis, and how they are thinking about its long-term effects. The paper aims to spark brainstorming and create dialogue about how business education can best respond to the crisis, particularly as it concerns its social and environmental effects.